The dynamic creep rupture of a secondary superheater tube in a 43 MW coal-fired boiler by the decarburization and multilayer oxide scale buildup on both sides. (July 2015) - Liu, William
Highlights: A dynamic creep mechanism has been proposed and verified through a case study. The creep mechanism transformed from intergranular fracture to transgranular rupture due to decarburization. The multilayer microstructures of the scales on both sides have been studied with ESEM/EDS. Analyses indicate that the scales on both sides were FeO due to the high formation temperatures. Analysis confirms that the rupture was a short-term severe overheating on the basis of long-term creep. Abstract: A dynamic creep mechanism has been proposed and verified through a case study. A secondary superheater tube burst occurred in a 43 MW coal-fired boiler. Microstructural examination indicates that the overheating temperatures reached 900 °C (above Ac3). The overheating duration was estimated to be 3 h by calculating with LMP formula. The 710 μm steam-side scale and 960 μm fireside scale built-up in the short time of overheating. The burst scenario was a short-term severe overheating on the basis of the long-term creep. The multilayer oxide scales on both sides have been studied with ESEM/EDS, indicating FeO. At 900 °C, full decarburization had gone throughout the tube. As the strength reduced due to the decarburization, the creep mechanism transformed from long-term intergranular creep to short-term transgranular rupture. The two types of dimples on the fractograph and two types of cracks in the microstructures confirmed the mechanism transformation. The overheating, the scale buildup and the decarburization constituted the full picture of the dynamic creep rupture.